High protein intake in human/maternal milk fortification for ≤1250 gr infants: intrahospital growth and neurodevelopmental outcome at two years - Biasini, Augusto; Monti, Fiorella; Laguardia, Maria Chiara; Stella, Marcello; Marvulli, Lucia; Neri, Erica (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the study: Extrauterine growth restriction and failure to thrive remain a major problem in Extremely Low Birth Weight infants. Nutritional support in preterm babies has the objective to improve the achieve rate of growth similar to those of the fetus in utero at the equivalent gestational age. The aim of the study was to evaluate feeding tolerance, intrahospital growth, neurological outcome and anthropometric data until 24 months of corrected age (mca) from different protein intake assumed by preterm babies <1250 g during their stay in NICU. Methods: The study evaluates auxological/neurodevelopmental outcomes until 24 months of corrected age (mca) in preterm infants with different protein intake (control group-CG: 3,5g Kg‾¹ perday; intervention group-PSG: 4,8g Kg‾¹ per day). Results: PSG group showed a significant higher length growth at 9 mca (p 0,04) and hearing/language score of Griffiths Mental Development Score (GMDS) at 12 (p 0,03) and 18 mca (p<0,05) comparing with CG. PSG-ELBW preterms showed an higher intrahospital head circumference (p 0,02) and length growth rate (p 0,04), greater Performance (p 0,04) and Hearing/Language (p 0,03) scores of GMDS at 3 and 12 mca. PSG-SGA preterms showed significantly higher scores in GMDS scores at 18 and 24 mca except for the locomotor domain. Conclusions: Supplemental enteral proteins lead to benefits of reduced postnatal growth restriction and better neurological outcome in preterm infants <1000 g and in those SGA <1250 g.